Pengaruh Celebrity Endorsement dan Emotional Value Terhadap Purchase Intention (Studi Pada Produk Endorse Outfit Wanita yang Dikenakan oleh Fadil Jaidi) - Kusumawardani, Febriana Lathifa; Iriani, Sri Setyo (Peneliti.net, 2023)
This paper analyses the influence of celebrity endorsement and emotional value on purchase intention on women’s endorsed outfit products used by Fadil Jaidi. This research uses quantitative data. The sampling technique used was judgemental sampling technique with 110 respondents. The research method used multiple linear regression analysis and data collection through online questionnaires by Whatsapp and Instagram Story. The results showed that celebrity endorsement has no positive and significant effect towards purchase intention. Meanwhile, emotional value has a positive and significant effect towards purchase intention. The implications based on this research show that customers will still pay more attention to the quality of the product they want to buy than paying attention to who is the endorser of the product. Additionally, before buying a product, customers will see the visuals of the product and look for information first, then customers will happy if they get the product.